Steroid-Free Immune Suppression Impairs Glycemic Control in a Healthy Cynomolgus Monkey. Issue 3 (March 2019) - Berman, Dora M.; Ruiz, Phillip; Blandino-Rosano, Manuel; Bernal-Mizrachi, Ernesto; Kenyon, Norma S.
The need for chronic immune suppression (IS) is one of the hurdles precluding widespread use of islet cell transplantation to restore glycemic control in patients with type 1 diabetes. We report the case of a healthy nonhuman primate (NHP) treated on and off for over 2.5 years with steroid-free IS, consisting of daclizumab induction and maintenance therapy with rapamycin and low dose tacrolimus. Treatment for 1 year resulted in a striking destabilization of glycemic control, with concomitant decreases in fasting c-peptide and insulin levels. Although these changes gradually reversed during a wash out period of 7 months, retreatment with the same therapy led to accelerated deterioration in glycemic control. Intravenous glucose tolerance and percentage of glycosylated hemoglobin testing further supported a dramatic effect on metabolic control. IS also led to decreases in weight during treatment. Histological evaluation of the pancreas revealed islet hyperplasia, with varying sizes and endocrine cell ratios that differed from normal islet composition, and parenchymal infiltration with adipose tissue. These deleterious effects of IS on glucose control and endocrine components in the native pancreas of a healthy NHP suggest that IS agents commonly utilized for islet transplantation may contribute to failure in islet allograft function in long-term transplant patients.